Difusión de Nb en Fe y algunas aleaciones de base Fe - Kurokawa, Susana; Ruzzante José Evaristo; Hey, Alfredo Martín; Dyment, Fanny (Comisión Nacional de Energía Atómica; Argentina, 1981)
Fil: Kurokawa, Susana Comisión Nacional de Energía Atómica; Argentina